Temporal Motivation Theory: Best Theory (Yet) to Explain Procrastination - Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2010)
Procrastination is frequently associated with postponing to make a decision or to act. Such phenom- enon could be found in almost all walks of life. Therefore a comprehensive understanding to allevi- ate it is urgently needed. This article compared four approaches which tend to explain procrastina- tion: psychoanalytic and psychodynamic, behavioristic, cognitive, and temporal motivation theory (TMT). As a recent and comprehensive approach, TMT was used as the main theoretical framework (Steel, 2007). TMT approach was believed to accommodate the other three previous theoretical ap- proaches. Further explanation and critical elaboration on TMT are discussed. Prokrastinasi seringkali dihubungkan dengan perilaku menunda mengambil putusan atau bertindak. Fenomena tersebut dapat dijumpai di hampir seluruh aspek kehidupan. Karena itu pemahaman yang lebih terpadu untuk mengatasinya sangatlah diperlukan. Artikel ini membandingkan empat pendekatan untuk menjelaskan prokrastinasi, yaitu psikoanalitik dan psikodinamik, perilakuan/behavioristik, kognitif, dan teori motivasi temporal (TMT). Sebagai pendekatan teoretis terkini dan terlengkap, TMT digunakan sebagai kerangka teoretis utama (Steel, 2007). Pendekatan TMT diyakini telah mewadahi ketiga pendekatan teoretis sebelumnya. Ulasan mengenai pendekatan TMT secara lebih lanjut beserta kritiknya telah dibahas.